Volvulus of the large colon in a neonatal foal - du Preez, S.; Trope, G. D.; Owens, C.; Hughes, K. J. (Equine veterinary education, 2018)
Summary A one‐day‐old Thoroughbred colt foal was presented for assessment of abdominal pain and reduced urine output. Physical examination of the foal revealed marked abdominal distension, mild tachycardia, tachypnoea and congested mucous membranes. A marked anechoic peritoneal effusion, intestinal hypomotility and mural thickening of the large colon were detected sonographically. Serosanguinous fluid was obtained by abdominocentesis. After haemodynamic stabilisation, the foal underwent general anaesthesia and exploratory laparotomy and a 720° volvulus of the large colon at the sternal and diaphragmatic flexures was identified. After correction of the volvulus, the intraoperative findings were consistent with nonviability of the affected portion of the colon. The owner declined partial colon resection and elected for euthanasia of the foal. Although rare in neonatal foals, large colon volvulus should be considered in foals with signs of abdominal pain, abdominal distension and ultrasonographic findings of colonic mural thickening and luminal distension.